Marketing untuk Menghadapi Masyarakat Ekonomi Asean (MEA) - Ahmad Yusron (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2018)
Abstract: A "whole" marketing process must take into account the transcendental element. Because, even though the marketer has been able to make customer smiles but with his actions to anger God the customer (Allah SWT). To speed up the economy in a country even to do international cooperation. MEA is a form of ASEAN economic integration in the sense that there is a free system among ASEAN countries. Indonesia and nine other ASEAN member countries agreed on the ASEAN Economic Community (MEA) Agreement. All ASEAN member countries will soon face a single, open market based on production. The establishment of the MEA aims to improve the welfare of all ASEAN members to face bank interest. It requires inter-sectoral policy coordination to seek solutions to prepare competit- able national industries. ASEAN needs to develop and have a competitive strategy. ASEAN needs to develop and have a great strategy and welcome MEA.Â Keywords: Marketing Islamic, Asean Economic CommunityÂ